Use of Phototherapy for Neonatal Hyperbilirubinemia Affects Cytokine Production and Lymphocyte Subsets - Kurt, Abdullah; Aygun, A. Denizmen; Kurt, A. Nese Citak; Godekmerdan, Ahmet; Akarsu, Saadet; Yilmaz, Erdal (Karger, 2009)
Background: Most studies regarding the influence of ultraviolet radiation on levels of inflammatory cytokines were conducted mainly in cultures of human keratinocytes or in laboratory animals. Few studies were also performed in human subjects. Objectives: To investigate the influence of the use of phototherapy on the levels of tumor necrosis factor (TNF)-alpha, interleukin (IL)-1 beta, IL-6, IL-8 such as cytokines expressed from keratinocytes and on the expression of some lymphocyte subsets in the prevention or treatment of neonatal hyperbilirubinemia. Methods: The study group included 21 term newborns with hyperbilirubinemia and the control group included 16 healthy term newborns. Blood samples were obtained from hyperbilirubinemic newborns before and at 72 h of exposure to phototherapy and from controls at the examination time. The levels of TNF-alpha, IL-1 beta, IL-6, IL-8 and lymphocyte subsets were measured in the samples using appropriate methods. Results: Serum TNF-alpha, IL-1 beta, IL-6, and IL-8 levels are similar in study and control groups. At 72 h of exposure to phototherapy serum TNF-alpha, IL-1 beta and IL-8 levels are significantly increased, while the serum IL-6 level at the same time is not significantly changed. Lymphocytes, lymphocyte subsets and white blood cell levels are similar in the study and control groups. Only, the percentage of CD3+ lymphocyte subset is significantly lower in newborns at 72 h of exposure to phototherapy. All other lymphocyte subsets are decreased by the exposure to phototherapy, and this change was not statistically significant. Conclusions: The results demonstrate that in addition to the well-known positive effect of phototherapy on the neonatal serum bilirubin level, this treatment can affect the function of the immune system in newborns via alterations in cytokine production. Copyright (C) 2008 S. Karger AG, Basel
Keywords: Hyperbilirubinemia, neonatal; Cytokine; Lymphocyte subsets; Immunity